Autonomic Nervous System Monitoring Heart Rate Variability - Aslanidis, Theodoros (IntechOpen, 2020)
Heart rate variability (HRV) is considered a reliable reflection of the many physiological factors modulating the normal rhythm of the heart. It reflects autonomic nervous system (ANS) function, and as such, it is used in numerous fields of medicine. Written by experts in the field, this book provides a comprehensive overview of HRV. The first section is dedicated to technical themes related to monitoring and the variables recorded. The second section highlights use of HRV in hypothermia. Finally, the third section covers general aspects of HRV application.